Underlying structure of e-learning readiness among Palestinian secondary school teachers - Trayek, Fuad A A; Tunku Ahmad, Tunku Badariah; Nordin, Mohamad Sahari; Dwikat, Mohammed AM; Abulibdeh, Enas Said Ali; Asmar, Muath; Md Sawari, Siti Salwa (EDP Sciences, 2016)
This paper reports on the results of an exploratory factor analysis procedure applied on the e-learning readiness data obtained from a survey of four hundred and seventy-five (N = 475) teachers from secondary schools in Nablus, Palestine. The data were collected using a 23-item, self-developed Likert questionnaire measuring e-learning readiness based on Chapnick's conception of the construct. Principal axis factoring (PAF) with Promax rotation applied on the data extracted four distinct factors supporting four of Chapnick’s e-learning readiness dimensions, namely technological, psychological, infrastructure, and equipment readiness. Together these four dimensions explained 56% of the variance. A reliability analysis produced high internal consistency estimates ranging between .81 (equipment readiness) and .91 (technological readiness) for the extracted factor structure. These findings provide sound empirical support for the construct validity of the items and for the existence of these four factors that measure e-learning readiness